Quantitative Assessment of Myocardial Ischemia in Multi-Vessel Coronary Artery Disease by Multimodal Stress Echocardiography with Semi-Supine Bicycle Ergometry - S. N. Koretskiy; O. M. Drapkina; F. B. Shukurov; D. K. Vasiliev (Рациональная фармакотерапия в кардиологии, 2020)
Stress echocardiography is a modern widely used method of noninvasive diagnosis of coronary heart disease and stratification of the risk of cardiovascular complications. In addition, exercise echocardiography is an important tool to clarify the localization of ischemia and establish a symptomassociated artery for management of patient with known coronary angiography data. This is especially important in multivessel lesions, the presence of an occluded artery or borderline stenosis. Currently, various stress agents are used for stress echocardiography in clinical practice: pharmacological drugs (dobutamine or adenosine), transesophageal or endocardial pacing, treadmill, semi-supine bicycle. To detect signs of ischemia usually used only visual estimation of local contractility in the two-dimensional gray-scale mode. Modern modes of myocardial imaging, such as speckletracking echocardiography or three-dimensional visualization, are practically not used. In the presented clinical case, the possibility of combining standard and modern imaging modes to clarify the localization and quantification of ischemia in multivessel coronary lesions, including chronic artery occlusion, is shown. As a stress agent, a semi-supine bicycle was chosen, the use of which allowed to obtain a qualitative image of the left ventricular myocardium at rest and at peak load, suitable for assessing deformation and threedimensional visualization. Evaluation of left ventricular myocardial deformation by speckle-tracking echocardiography was more accurate than standard diagnosis in detecting signs of ischemia in a patient with multivessel lesions. Three-dimensional imaging was inferior in sensitivity to speckletracking stress echocardiography and, at present, seems to have more research value.